It's Garry Shandling's book - Shandling, Garry (Random House, 2019)
"Garry Shandling was a singular trailblazer in the comedy world. His two hit shows, It's Garry Shandling's Show and The Larry Sanders Show, broke new ground and influenced future sitcoms like 30 Rock and Curb Your Enthusiasm, and his stand-up laid the foundation for a whole generation of comics. There's no one better to tell Garry's story than Judd Apatow--Garry gave Judd one of his first jobs on The Larry Sanders Show and remained Apatow's mentor for the rest of his life--and the book expands on his brilliant HBO documentary, The Zen Diaries of Garry Shandling, which won the 2018 Emmy Award for Best Documentary. Here, Apatow has gathered up journal entries, photographs, and essays for a close-up look at the artist who turned his gaze back onto the world of show business to create a new language of comedy writing. Beyond his success, though, Shandling struggled with fame, the industry of art, and the childhood loss of his brother, which forever affected his personal and professional life. A heartwrenching letter to his brother, written in his journal as an adult, is the emotional center of this book that runs the gamut from hilarious observations to deep spiritual inquest. His diaries show Shandling to be very self-aware and insightful, revealing a lesser known philosophical and spiritual side. Contributions by comedians and other leading lights of the industry, including people who grew up with Shandling and many who owe their careers to him, along with never-before-seen pieces of scripts that never made it to production and bits of stand-up from Shandling's writing that he never performed, shed new light on every facet of his life and work. This book is a testament to the lasting impact of Garry Shandling"--